(untitled) (Iraqi Journal of Medical Sciences, 2021)
Background:Helicobacter pylori (H. pylori) infection had been criticized for many deleterious effects and had been amalgamated to iron deficiency by many authors, frequently based on correlative rather than direct relationship studies and often opposed by others. Objective: To evaluate the role of H. pylori infection in the etiology of iron deficiency anemia and to study the impact of the bacterial eradication on the response to iron therapy. Methods:The current study represents an interventional prospective study and involved 52 non-pregnant females with iron deficiency anemia. All patients were tested for the presence of active H. pylori infection by stool antigen test and they followed after one month of iron therapy. Patients with positive H. pylori infection followed for another month after eradication of H. pylori and iron therapy. Results: Fifteen patients (28.85%) were positive for H. pylori. Hematological and biochemical data were not different among both groups (H. pylori positive and negative) at presentation despite significant better response among H. pylori negative individuals. Continuation of iron therapy after eradication of H. pylori infection improve the response to therapy significantly. Conclusion: Eradication of H. pylori enhances the response to iron therapy significantly. Keywords: Iron deficiency anemia, H. pylori, iron therapy, eradication Citation: Eissa AA, Mirza SS. The relevance of Helicobacter pylori Infection to iron deficiency anemia in Duhok City. Iraqi JMS. 2021; 19(1): 33-38. doi: 10.22578/IJMS.19.1.5